Synthesis and characterization of palm fatty hydrazide derivatives - Ahmad, Norashikin (2012)
Hydrazide derivatives have been synthesized from methyl esters, hydrazones and vegetable oils. They are important due to their diverse applications in pharmaceutical products, detergents as well as in oil and gas industries. The chemical synthesis of fatty hydrazides is well-established; however, few publications described the synthesis of fatty hydrazide derivatives, particularly, when produced from refined, bleached and deodorized palm olein. Here, the synthesis and characterization of fatty hydrazide derivatives are reported. Besides, palmityl hydrazide derivative synthesized from palmityl hydrazide was used as reference. The fatty hydrazides derivatives were characterized using a Fourier transform infrared(FTIR), gas chromatography (GC) and nuclear magnetic resonance (NMR) spectroscopy. The synthesis of N,N-dimethyl fatty hydrazides was carried out at 100oC in dioxane for 6 hours with the molar ratio between hydrazide, dimethyl sulfate and potassium hydroxide was 1:1:1. The proton NMR confirmed the product obtained was N,N-dimethyl fatty hydrazides. Other fatty hydrazide derivatives were cationic surfactants prepared using N,N-dimethyl fatty hydrazides. The surface tensions of these cationic surfactants vary according to the types of acyl chlorides. Lower surface tension was recorded for cationic surfactants prepared with acyl chloride with phenyl group. In addition, cationic surfactant can also be prepared from reaction between acyl chlorides and fatty hydrazides. Hence, fatty hydrazide derivatives from palm olein were successfully prepared and characterized.